The experimental investigation of precise intelligent thermoanemometric flow meter for biofuel - Безвесільна, Олена Миколаївна; Черепанська, Ірина Юріївна; Сазонов, Артем Юрійович; Нечай, Сергій Олексійович (Technology audit and production reserves, 2016)
The paper presents the constructions of fine thermoanemometric flow meter for biofuel (TAFM) as well as the results of its experimental research. The flow meter contains neural processor to compensate dynamic errors because of theirs essential value. Neural processor using as a part of TAFM significantly raises its accuracy. The latter is confirmed by the results of experimental researches on the specially designed unit, particularly by calibration and verification. The results of experimental researches determine that during the work of TAFM on biofuel when changing in the ranges of temperatures 0 … 180 ºC the errors do no exceed 0,2 %. It is stated that the reasons for TAFM errors can be the errors of etalon sensors and thermal sensors which are a part of TAFM, the changes of fuel volume, measuring tank volume also influence the biofuel temperature as well as the environment temperature. This development can be used for accounting consumption of biofuel of vehicle engine. This approach will significantly improve their conditions of work in comparison with diesel fuel, decrease biofuel consumption as well harmful engine emissions.